Tendência à sustentabilidade ecológica de loteamentos no município de Bauru/SP - Garbelotti, Paulo Roberto Gervasio (2016)
Cities, big poles of development and also generators of social and spatial segregation, are suffering the pressure on urban systems and sanitation because of uncontrolled urbanization and industrialization by the rural exodus, causing irregular occupations in environmentally fragile areas. In this work ,it was searched the assessment of sustainability in its several aspects, through land fragmentation project analysis in the city of Bauru, Sao Paulo, selected according to criteria of location, size of business, size of lots, date of approval, surveys and survey data, including checking the implementation of it. With the acquisition of data, it was promoted comparative analysis between the project approved and its implementation and also between the several aspects of land division recorded on the projects analyzed using as reference the "PESMU - Sustained Urban Planning of Urban," through their subcomponents, allowing the assessment of the trend of ecological sustainability. Knowing these aspects of ecological sustainability and beyond for situations close to the sites and analyzed for parameters for setting up new ventures and lots in the city, especially when the issues of the region and the deployment are similar, with the aim of improving the inhabitants quality of life of the place approached.